1997
DOI: 10.1074/jbc.272.19.12305
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Leukotriene C4 in γ-Glutamyl Transpeptidase-deficient Mice

Abstract: LTC 4 -converting activity has a tissue distribution different from GGT with highest activity in spleen followed by small intestine, kidney, and pancreas and lower activity in liver and lung. The activity is membrane-bound and is inhibited by acivicin, a known inhibitor of GGT. The enzyme was partially purified from the small intestine of GGT-deficient mice by papain treatment and gel filtration chromatography. The partially purified fragment released by papain has an apparent molecular mass of 65-70 kDa and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(106 citation statements)
references
References 25 publications
4
100
2
Order By: Relevance
“…The remaining cystinyl-bis-glycine and its conversion products were then incubated with 5 l of 10 mM DTT to convert them to cysteinyl glycine and cysteine. The samples were derivatized with 2,4-dinitroflurobenzene and analyzed by reversed-phase ion exchange HPLC as described previously (8,36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining cystinyl-bis-glycine and its conversion products were then incubated with 5 l of 10 mM DTT to convert them to cysteinyl glycine and cysteine. The samples were derivatized with 2,4-dinitroflurobenzene and analyzed by reversed-phase ion exchange HPLC as described previously (8,36).…”
Section: Methodsmentioning
confidence: 99%
“…They are generated by the conjugation of the epoxide intermediate LTA 4 with glutathione (GSH) to form LTC 4 (6). This compound is degraded by the action of ␥-glutamyl transpeptidase (GGT, EC 2.3.2.2) and the more recently characterized enzyme ␥-glutamyl leukotrienase; these enzymes cleave the ␥-glutamyl moiety from LTC 4 to form the cysteinyl glycine conjugate of LTA 4 (7,8). LTD 4 is then converted to LTE 4 by a dipeptidase.…”
mentioning
confidence: 99%
“…GGT also cleaves exogenous glutathione for use as a cysteine and nitrogen source in Escherichia coli, yeast, and mammalian cells (3)(4)(5). In mammals, GGT is involved in the conversion of leukotriene C 4 to D 4 , although GGT is not the only enzyme that catalyzes this reaction (6,7). GGT is a key enzyme in glutathione metabolism, and genetic diseases of GGT deficiency, including glutathionemia and glutathionuria, are associated with mental retardation (8,9).…”
mentioning
confidence: 99%
“…HPLC was used to monitor the reactions with LTC 4 , GSH and GSSG; spectrophotometric analysis was used for GpNA andglutamyl-4-methoxy-2-naphthylamide. It was concluded that there was enzyme activity present that was able to cleave LTC 4 , and was named γ-glutamylleukotrienase (GGL) (Carter et al, 1997). Other physiological donor substrates such as GSH, GSSG, or chromogenic donor substrates such as GpNA and -glutamyl-4-methoxy-2-naphthylamide were not hydrolyzed by GGL (Carter et al, 1997).…”
Section: Other Enzymes With γ-Glutamyltransferase-like Activitymentioning
confidence: 99%
“…Carter and colleagues studied GGT-knock-out mice that were generated by embryonic stem cell technology (Lieberman et al, 1996;Carter et al, 1997). A recombinant plasmid carrying the mouse GGT-knock-out gene was transfected into embryonic stem cells; transformed embryonic stem cells were inserted into mouse blastocysts; blastocysts were implanted into a female mouse (Lieberman et al, 1996).…”
Section: Other Enzymes With γ-Glutamyltransferase-like Activitymentioning
confidence: 99%